Mobile Phone-based Information Systems for Empowerment: Opportunities for Ready-made Garment Industries. Issue 1 (2nd January 2021) - Ahad, Taimur; Busch, Peter; Blount, Yvette; Picoto, Winnie
ABSTRACT: The purpose of the study is to present a Mobile information System (MbIS) framework for Bangladeshi ready-made garments (RMG), as there is growing concern RMG owners and workers require empowerment using technology. Our study employed a qualitative research methodology based on interviews with RMG owners, workers, non-government organizations (NGOs) and IT experts. The interview data suggested MbIS has the potential to empower RMG owners/workers. MbIS-enabled empowerment suggests access to information, competency, impact; self-determination and meaning are empowerment components for RMG workers. Improved communication, the opportunity to access employee regulations, access to health and safety information, increased confidence with regard to ability and professional development opportunities are potential empowerment outcomes of using MbIS. This is one of the few papers examining MbIS comprehensively for worker empowerment, as most literature approaches the matter from the consumer standpoint, not in an organizational setting. The study contributes by providing practical knowledge to the RMG, government, and development organizationsin empowerment processes, components and empowerment outcomes using MbIS for RMG owners/employees. Other garment-producing developing countries may also gain insight into how to empower RMG workers using MbIS.